2022
DOI: 10.3389/fnut.2022.808346
|View full text |Cite
|
Sign up to set email alerts
|

High Protein Diets Improve Liver Fat and Insulin Sensitivity by Prandial but Not Fasting Glucagon Secretion in Type 2 Diabetes

Abstract: Glucagon (GCGN) plays a key role in glucose and amino acid (AA) metabolism by increasing hepatic glucose output. AA strongly stimulate GCGN secretion which regulates hepatic AA degradation by ureagenesis. Although increased fasting GCGN levels cause hyperglycemia GCGN has beneficial actions by stimulating hepatic lipolysis and improving insulin sensitivity through alanine induced activation of AMPK. Indeed, stimulating prandial GCGN secretion by isocaloric high protein diets (HPDs) strongly reduces intrahepati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
3
4
0
Order By: Relevance
“…We assessed parameters of glucagon metabolism only during fasting, overlooking postprandial excursions, which may contribute substantially to disease, as shown for glucose metabolism [ 40 ]. In a similar study [ 23 ] closely resembling the isocaloric study presented here, individuals with type 2 diabetes followed a 6-week isocaloric high-protein diet that yielded no changes in fasting levels of glucagon, mirroring our findings. Nevertheless, the authors [ 23 ] also assessed the effect of a mixed-meal tolerance test following 6 weeks’ high-protein feeding and showed a noteworthy reduction in postprandial alanine levels, while postprandial glucagon levels remained unchanged, indicative of improved glucagon signaling.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…We assessed parameters of glucagon metabolism only during fasting, overlooking postprandial excursions, which may contribute substantially to disease, as shown for glucose metabolism [ 40 ]. In a similar study [ 23 ] closely resembling the isocaloric study presented here, individuals with type 2 diabetes followed a 6-week isocaloric high-protein diet that yielded no changes in fasting levels of glucagon, mirroring our findings. Nevertheless, the authors [ 23 ] also assessed the effect of a mixed-meal tolerance test following 6 weeks’ high-protein feeding and showed a noteworthy reduction in postprandial alanine levels, while postprandial glucagon levels remained unchanged, indicative of improved glucagon signaling.…”
Section: Discussionsupporting
confidence: 86%
“…In a similar study [ 23 ] closely resembling the isocaloric study presented here, individuals with type 2 diabetes followed a 6-week isocaloric high-protein diet that yielded no changes in fasting levels of glucagon, mirroring our findings. Nevertheless, the authors [ 23 ] also assessed the effect of a mixed-meal tolerance test following 6 weeks’ high-protein feeding and showed a noteworthy reduction in postprandial alanine levels, while postprandial glucagon levels remained unchanged, indicative of improved glucagon signaling. Indeed, glucagon is also important for the postprandial regulation of glucose and amino acid metabolism [ 9 ] and perhaps also lipid metabolism [ 41 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Studies in people with type 2 diabetes (T2D) have observed similar increases in the gut hormone GLP-1 as well as a pancreatic polypeptide (PYY)with high protein diets, which have been shown to suppress the rate of gastric emptying and, therefore, the rate at which blood glucose concentrations increase following a meal [46,47]. Additionally, high protein diets have been shown to improve insulin sensitivity via reductions in intra-hepatic liver triglycerides and increases in post-meal glucagon secretion among people with T2D [48][49][50][51]. It is possible that improvements in insulin sensitivity and reductions in gastric emptying rate associated with elevated protein intakes may contribute to the improvements in post-exercise glycemia observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relative contributions of alpha- to beta-cell cross talk and diminished inhibition of glucagon secretion by insulin resistance or deficiency and increased AA stimulation is presently unclear. Both fatty liver and insulin resistance correlate well with glucagon levels in plasma [ 105 ].…”
Section: Glucagon and Amino Acid Metabolismmentioning
confidence: 99%